A Cross-Sectional Assessment of Conflict, Nutrition and Health Among Children Under Five in Cameroon - Cynthia Fonta; David Gordon; Timothy F. Brewer; Zoi Toumpakari (Journal of Community Medicine and Public Health Research, 2026)
Studies have shown inconsistent effects of conflict on children’s nutritional status. Cross-border and internal conflicts may harm children’s well-being more than in stable regions. This analysis examines the relationship between conflict zones, undernutrition as measured by the Composite Index of Anthropometry Failure (CIAF), and anaemia in Cameroon. The study used Cameroon’s 2018 Demographic and Health Survey (CDHS), sampling 4,498 children under five with complete anthropometry data. We performed a multivariate logistic regression analysis to test the association of conflicts, food insecurity (FI), and other covariates with undernutrition and anaemia. In univariate analyses, rural residence, living in conflict zones, water/sanitation deprivation, and lack of maternal education were associated with undernutrition, while female sex and household wealth were protective. In multivariate analyses, residing in a conflict area was significantly associated with undernutrition (OR=1.7; 95% CI: 1.4-2.0), whereas female sex remained protective against undernutrition (OR=0.7; 95% CI: 0.6-0.9). Increasing household wealth was associated with lower rates of undernutrition (OR=0.3; 95% CI: 0.2-0.5) and anaemia (OR=0.6; 95% CI: 0.4-0.8). Higher maternal education remained protective against undernutrition (OR=0.8; 95% CI: 0.6-0.9) and anaemia (OR=0.6; 95% CI: 0.5-0.8), and increasing childhood age reduced the odds of anaemia (OR=0.7; 95% CI: 0.6-0.9). Living in a household with unimproved/surface water increased the odds of anaemia (OR=1.3; 95% CI: 1.1-1.5). Food insecurity was not associated with undernutrition or anaemia. Living in a conflict zone adversely impacts the nutritional status of children in Cameroon. These findings highlight the need for nutrition- focused interventions in conflict-affected areas.